Narrative Therapy of the Sporting Body - Calabrese, Stefano; Nedkova, Denitza (Testo e Senso, 2019)
The great significance of the narrative activity in the re-establishment of the injured and restored sporting body, as well as an effective athletic identity, aims to be the core of the present paper. Several types of autobiographical stories of disability caused by physical exertion during sport are the base of the study. It starts by illustrating the importance of the opposite relation between the self and the body – namely, entirely sports’ dedicated fictional and non-fictional novel literature, exemplified by the memories of the world-renowned writer Haruki Murakami, who happens also to be a semi-professional distance runner. We highlight the presence of specific narrative typologies progressively generated by the harm and rehabilitation, by the physical suffering and the psychological sacrifice to get to the more positive stories of restoration and recuperation, all linked by the agencies of the body/identity interaction with the reality. The analysis of these narratives and the role they play within the healing process – physical, psychological or both – leads to point out the narrator's ability to acquire a phenomenological consideration of the (injured) body. These stories allow to maintain firm the athlete’s identity facing the fear - revealed from the injury - of the sport itself. Hence, through the self-teller and co-teller narrative exchange, the harmed one reaches the critical to the rehabilitation high degree of intra and inter subjectivity and, above all, manages to give a shape of the negative experience via narrating it and therefore facing it.